2018
DOI: 10.17853/1994-5639-2018-2-32-59
|View full text |Cite
|
Sign up to set email alerts
|

The Practices of Project-Based Learning Technique Application: Experience of Different Countries

Abstract: Introduction. In the educational systems of different countries, much experience has been gained regarding the use of project-based learning. This method is an alternative to traditional lecture-based learning: it helps to pull together a theoretical training material with real life; additionally, it changes the roles of pupils and teachers: students become active fully-competent subjects of an educational process, whereas teachers organize, supervise and direct this process, but do not transfer readily availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
(7 reference statements)
0
14
0
1
Order By: Relevance
“…The analysis of the practice of project training described in a number of Russian and foreign articles [2]- [8], [10]- [39] (the list of published scientific papers related to the topic of the article is not complete and presents the most important and latest studies), has revealed the following advantages (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the practice of project training described in a number of Russian and foreign articles [2]- [8], [10]- [39] (the list of published scientific papers related to the topic of the article is not complete and presents the most important and latest studies), has revealed the following advantages (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The sixth requirement is the integrated and systematic nature of project activities. According to Russian and foreign scientists, in particular, S. V. Ivanova, L. S. Pastukhova [7], A. P. Kazun, L. S. Pastukhova [8], Y.C. Hsu, Y. M. Shiue [28], L.A. Jacques [30], non-systemic and fragmented project activities can seriously slow down the effective implementation of the project method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The critics of W. Kilpatrick pointed out that his concept, at least in its original form, is more a philosophical justification of the new method than a specific set of tools (Kazun & Pastukhova, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Анализ научных источников [5,7,11,16,[21][22][23]29] позволил нам выявить и сформулировать следующие отличительные признаки метода проектов по сравнению с другими инновационными методами и технологиями для обоснования целесообразности его применения в образовательном процессе вуза с целью развития ключевых общих и профессиональных компетенций:…”
unclassified